Effects of tear size and location on predictions of supraspinatus tear propagation. (8th February 2018) - Miller, R. Matthew; Thunes, James; Musahl, Volker; Maiti, Spandan; Debski, Richard E.
Abstract: Rotator cuff tears remain a significant clinical problem with a high incidence rate and severe clinical burden. Previous computational models developed to study rotator cuff tears have not modeled tissue damage and tear propagation. The objective of this study was to predict tear propagation for various combinations of tear size and location using an experimentally validated finite element model of supraspinatus tendon. It was hypothesized that larger rotator cuff tears propagate at lower loads than smaller tears, and that posterior tears require higher loads to propagate than anterior tears. Using a previously validated computational model of supraspinatus tendon, tears of size 0.5–1.5 cm were introduced to the tendon geometry in the anterior, middle, and posterior tendon thirds. Cohesive elements were assigned subject-specific failure properties and used to model tissue damage and tear propagation. A displacement of 5 mm was applied to the medial tendon edge to induce tear propagation. Model outputs included critical load required to propagate the tear, and principal stress and maximum principal strain at the anterior and posterior tear tips. For all tear sizes, posterior tears required the highest loads to propagate (247–567 N). Anterior tears generally required the least load to propagate (171–280 N). Stress and strain were larger on the articular side (maximum 33.9% articular strain vs 27.8% bursal strain). Overall, larger tears located in the anterior supraspinatus tendon that interrupt the rotator cable are most at risk for tear propagation, and should be carefully followed by clinicians when considering treatment options.